1984
DOI: 10.1177/019262338401200309
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Mechanisms of Chemical Carcinogenesis: The Role of the NADPH Pool in the Benzo(a)pyrene Activation

Abstract: A EST RA CT Human lymphocytes and human skin fibroblasts isolated in vilro from subjects carrying the Mediterranean variant of glucose-6-phosphate dehydrogenase (CCPD) exhibit an 86-87% decrease of this enzymatic activity. This is coupled with 51% and 61% decreases of the NADPH/NADP+ ratio in the GCPD-deficient human lymphocytes (HL) and human skin fibroblasts (HSF), respectively. There also occurs a 63-67% decrease of the hexose monophosphate shunt (HMS) in the deficient cells. Incubation with 0.1 mM methylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…All of these effects may result from a limitation of intracellular NADPH supply stemming from a reduction in G6PD activity. Moreover, resistance to benzo[a]pyrene cytotoxicity can be mimicked in normal fibroblasts by treatment with DHEA (31)(32)(33)(34). Epidemiologic evidence also supports this hypothesis since individuals with G6PD deficiency may be more resistant to developing cancer than normal individuals from the same geographical area (for reviews, see refs.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…All of these effects may result from a limitation of intracellular NADPH supply stemming from a reduction in G6PD activity. Moreover, resistance to benzo[a]pyrene cytotoxicity can be mimicked in normal fibroblasts by treatment with DHEA (31)(32)(33)(34). Epidemiologic evidence also supports this hypothesis since individuals with G6PD deficiency may be more resistant to developing cancer than normal individuals from the same geographical area (for reviews, see refs.…”
Section: Discussionmentioning
confidence: 94%
“…Cells from individuals with the severe Mediterranean variant of G6PD deficiency show depression of metabolism, DNA-binding and cytotoxicity of benzo[a]pyrene. Furthermore, G6PD-deficient granulocytes generated lower amounts of superoxide in response to phorbol esters (31,32). All of these effects may result from a limitation of intracellular NADPH supply stemming from a reduction in G6PD activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in our laboratory has demonstrated that cultures of human skin fibroblasts (HSF) and human lymphocytes (HL) carrying the Mediterranean variant ofG6PD are more resistant than norma1 HSF and HL to the toxic effects of BaP (8)(9)(10)23). G6PD-deficient HSF appear to be less prone than normal cells to in vitro transformation by BaP, as assessed by the loss of anchorage-dependence (8).…”
Section: Introductionmentioning
confidence: 99%
“…G6PD-deficient HSF appear to be less prone than normal cells to in vitro transformation by BaP, as assessed by the loss of anchorage-dependence (8). It has been observed that G6PD-deficient HSF and HL exhibit a great decrease of the hexose monophosphate shunt, either stimulated or not by methylene blue, as well as of the NADPH/NADP+ ratio (8)(9)(10)23). Moreover, NADPH-cytochrome reductase and BaP hydroxylase activities were found to be lower in homogenates of G6PD-deficient HL, * Presented at the Third Sardinian International Symposium, when tested in a reaction system containing exogenow G6P and NADPf and endogenous G6PD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation